Preference of Bemisia tabaci biotype B oviposition in cotton cultivars - Toscano, Luciana Cláudia; Santos, Terezinha Monteiro dos; Júnior, Arlindo Leal Boiça (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the oviposition preference to Bemisia tabaci biotype B in cotton cultivars. In free choice test, Deltapine Acala 90, pilose cultivar, was the most preferred for oviposition (6.11 eggs/cm2 of leaf) in relation to Antares, smooth leaf, (0.49 eggs/cm2 of leaf). The oviposition preference of whitefly was not influenced by cultivars in no-choice test. The oviposition preference index classified Deltapine Acala 90 as stimulant, while Antares was classified as deterrent to insect oviposition, showing oviposition non-preference type to B. tabaci biotype B.
Keywords: cotton; resistance to injurious factors; pest insects; infestation; reproduction